Pengaruh Penetration Index Terhadap Karakteristik Marshall Laston Menggunakan Limbah Styrofoam dan PVC - Ratna Yuniarti; I Dewa Made Alit Karyawan (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2021)
The performance of road pavement is strongly determined by material used in asphalt mixture. However, it is occasionally found that asphalt used in hot mix asphalt did not fulfill softening point requirement. On the other hand, the amounts of waste styrofoam and PVC are tend to increase and need a large space for its handling. Therefore, it is necessary to improve the quality of asphalt by using waste styrofoam and PVC. This article aims to review the performance of asphalt concrete using waste styrofoam and PVC as asphalt modifier based on the value of its penetration index. Styrofoam modified asphat was made by mixing asphalt penetration grade 60/70 with 0%, 2%, 4% and 6% waste styrofoam, meanwhile the percentages of waste PVC as asphalt modifier were 1%, 2%, 3% and 4%, respectively. The properties analyzed are Marshall stabiliy, flow, Marshall Quotient, Marshall immersion and retained strength index. From the analysis, it can be concluded that the use of waste styrofoam and PVC increase modified asphalt penetration index, and its penetration index significantly affect the properties of asphalt concrete